Sensitive Detection of Pre-Existing BCR-ABL Kinase Domain Mutations in CD34+ Cells of Newly Diagnosed Chronic-Phase Chronic Myeloid Leukemia Patients Is Associated with Imatinib Resistance: Implications in the Post-Imatinib Era - Iqbal, Zafar; Aleem, Aamer; Iqbal, Mudassar; Naqvi, Mubashar Iqbal; Gill, Ammara; Taj, Abid Sohail; Qayyum, Abdul; ur-Rehman, Najeeb; Khalid, Ahmad Mukhtar; Shah, Ijaz Hussain; Khalid, Muhammad; Haq, Riazul; et al. (PloS one, 2013)
BCR-ABL kinase domain mutations are infrequently detected in newly diagnosed chronic-phase chronic myeloid leukemia (CML) patients. Recent studies indicate the presence of pre-existing BCR-ABL mutations in a higher percentage of CML patients when CD34+ stem/progenitor cells are investigated using sensitive techniques, and these mutations are associated with imatinib resistance and disease progression. However, such studies were limited to smaller number of patients. We investigated BCR-ABL kinase domain mutations in CD34+ cells from 100 chronic-phase CML patients by multiplex allele-specific PCR and sequencing at diagnosis. Mutations were re-investigated upon manifestation of imatinib resistance using allele-specific PCR and direct sequencing of BCR-ABL kinase domain. Pre-existing BCR-ABL mutations were detected in 32/100 patients and included F311L, M351T, and T315I. After a median follow-up of 30 months (range 8-48), all patients with pre-existing BCR-ABL mutations exhibited imatinib resistance. Of the 68 patients without pre-existing BCR-ABL mutations, 24 developed imatinib resistance; allele-specific PCR and BCR-ABL kinase domain sequencing detected mutations in 22 of these patients. All 32 patients with pre-existing BCR-ABL mutations had the same mutations after manifestation of imatinib-resistance. In imatinib-resistant patients without pre-existing BCR-ABL mutations, we detected F311L, M351T, Y253F, and T315I mutations. All imatinib-resistant patients except T315I and Y253F mutations responded to imatinib dose escalation. Pre-existing BCR-ABL mutations can be detected in a substantial number of chronic-phase CML patients by sensitive allele-specific PCR technique using CD34+ cells. These mutations are associated with imatinib resistance if affecting drug binding directly or indirectly. After the recent approval of nilotinib, dasatinib, bosutinib and ponatinib for treatment of chronic myeloid leukemia along with imatinib, all of which vary in their effectiveness against mutated BCR-ABL forms, detection of pre-existing BCR-ABL mutations can help in selection of appropriate first-line drug therapy. Thus, mutation testing using CD34+ cells may facilitate improved, patient-tailored treatment.